Achieving exceptionally high strength in Mg3Al1Zn-0.3Mn extrusions via suppressing intergranular deformation. (November 2018) - Zeng, Z.R.; Zhu, Y.M.; Liu, R.L.; Xu, S.W.; Davies, C.H.J.; Nie, J.F.; Birbilis, N.
Abstract: Exceptionally high strength Mg3Al1Zn-0.3Mn wt.% (AZ31) is demonstrated herein, revealing a yield strength of 380 MPa in both tension and compression, for extrusions prepared at 175 °C. Extruded AZ31 nominally has a low-to-moderate yield strength amongst typical magnesium (Mg) extrusion alloys, generally less than 250 MPa. The low strength is predominantly due to a large grain size and the absence of effective precipitation strengthening. In this study, AZ31 was extruded at different temperatures to reveal an exceptionally high strength with ultrafine grains of 0.65 μm in diameter. To reveal the origin of high strength in this AZ31 alloy, the microstructure of AZ31 was compared with those of Mg1Zn alloy and pure Mg with similar grain size and textures. The solute atoms were identified to be the key to alloy strengthening (∼210 MPa). In contrast to grain boundary sliding, grain boundary migration and grain rotation that is observed submicron-grained pure Mg; the solute in submicron-grained AZ31 suppressed such intergranular deformation modes, with the grain boundaries in submicron-grained AZ31 providing significant strengthening (via the Hall-Petch relationship). In the high-strength AZ31 presented, Al reacts with Mn to form uniformly distributed particles, whilst Zn solute atoms segregated to grain boundaries, the latter posited to stabilize the boundaries of submicron grains by reducing grain boundary energy and thus suppressing the intergranular deformation. The results herein reveal high strength Mg-alloys are readily achievable, the related concepts of which have implications for numerous Mg alloy systems. Graphical abstract: Image 1